Risk factors of LEEP margin positivity and optimal length of cervical conization in cervical intraepithelial neoplasia - Cong, Qing; Yu, Yi; Xie, Yu; Li, Yanyun; Sui, Long (Frontiers in Oncology, 2023)
Background The conization length for cervical precancerous lesions is essential for treatment but is left undetermined. This study aims to explore the reasonable and optimal conization length in patients with different types of cervical transformation zones (TZs) to reach the treatment outcome of margin negative in the surgery. Methods From July 2016 to September 2019, a multi-center prospective case–control study with or suspicion of cervical precancer was enrolled from five medical centers in Shanghai, China. The clinical characteristics, cytology, human papillomavirus (HPV), histopathology, and details of cervical conization were recorded. Results A total of 618 women were enrolled in this study; 6.8% (42/618) had positive internal (endocervical and stromal) margins and 6.8% (42/618) had positive external (ectocervical) margins of loop electrosurgical excision procedure (LEEP) specimen. Comparing the positive internal margin group with the negative group, age (p = 0.006) and cytology (p = 0.021) were significantly different. Multivariate logistic regression analysis showed that the risk factors for positive internal margin were cytology ≥ high-grade squamous intraepithelial lesion (HSIL) (odds ratio (OR) 3.82, p = 0.002) and age (OR 1.11, p < 0.001). The positive internal margin rate was 2.7%, 5.1%, and 6.9% in TZ1, TZ2, and TZ3, respectively, while the positive external margin was 6.7%, 3.4%, and 1.4%, respectively. In the TZ3 group, the HSIL positive internal margin of the 15–16-mm group (10.0%, 19/191) was significantly greater than in TZ1 (2.7%, 4/150) (p = 0.010) and TZ2 (5.0%, 9/179) (p = 0.092); when excision length increases to 17–25 mm, the positive internal margin rate dramatically decreased to 1.0% (1/98). Conclusion A cervical excision length of 10–15 mm is reasonable for TZ1 and TZ2 patients, while 17–25 mm is optimal for TZ3 excision with more negative internal margins.